The impact of industrial synergistic agglomeration on residents’ health levels - Qi, Di; Xu, Wenhan (Frontiers in Public Health, 2025)
IntroductionThis study investigates the impact of industrial synergistic agglomeration on residents’ health levels in China. It explores how green and traditional industry agglomeration models influence residents’ health levels outcomes and identifies the underlying mechanisms driving these effects.MethodsUsing panel data from 283 prefecture-level cities and above in China from 2003 to 2020, the study applies the Generalized Spatial Two-Stage Least Squares (GS2SLS) method. This approach allows for a systematic analysis of both direct and spatial spillover effects, focusing on the comparative impacts of green and traditional industrial agglomeration models.Results(i) Spatial Effects: Residents’ health levels exhibits a significant positive spatial effect, with public health improvements in one city positively influencing neighboring cities.(ii) Industrial Agglomeration: Industrial synergistic agglomeration has a stronger positive impact on residents’ health levels compared to single-industry agglomeration.(iii) Mechanisms: The effect of industrial synergistic agglomeration on residents’ health levels operates through three primary mechanisms:- Population Agglomeration Effects: Enhanced population clustering contributes to better public health services.- Media Dissemination Effects: Improved information dissemination raises public health awareness.- Income Growth Effects: Increased income levels drive better access to healthcare and lifestyle improvements.(iv) Model Comparison: Green industry synergistic agglomeration proves more beneficial for residents’ health levels improvement than traditional industry agglomeration.DiscussionThe findings highlight the critical role of industrial synergistic agglomeration, particularly in green industries, in promoting residents’ health levels. Policymakers are encouraged to prioritize strategies fostering green industry clustering and to leverage the identified mechanisms to amplify public health benefits across regions.